Efek protektif ekstrak etanol Bidens pilosa L. terhadap sistem imun tubuh berdasarkan histologis limpa Rattus norvegicus yang diinduksi alkohol - Marpaung, Mieky Grasiaella; Silitonga, Melva (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
This study aims to determine the protective activity of Bidens pilosa L. leaf ethanol extract (EEDK) on the immune system based on the white pulp diameter, and histopathology of the spleen of white rats given alcohol. The study was conducted experimentally using a completely randomized design (CRD), with treatments divided into 5 groups: negative control (K-) without EEDK or alcohol administration, positive control (K+) administered 10 ml/kg body weight of alcohol, treatment 1 (P1) administered 250 mg/kg body weight of EEDK and 10 ml/kg body weight of alcohol, treatment 2 (P2) given 500 mg/kgbb EEDK and 10 ml/kgbb alcohol, and treatment 3 (P3) given 750 mg/kgbb EEDK and 10 ml/kgbb alcohol. EEDK was administered 1 hour after alcohol administration and was given orally every day for 43 days. The parameters observed in this study were diameter of the white pulp, and histopathology of the white rat spleen. The observation data were analyzed using one-way ANOVA and followed by a post hoc test with the DMRT test to see the differences between treatments. The results showed that the ethanol extract Bidens pilosa L. potential as an immunomodulator by increasing the diameter of the white pulp of the spleen, and had a significant effect on spleen histology by showing protective activity with a decrease in the level of spleen tissue damage due to alcohol, particularly tissue fibrosis, lymphocyte apoptosis, and necrosis (p£0.05).